Correction of Coronal Deformity and Intercompartmental Imbalance through Bone Resection - Roche, Martin; Law, Tsun Yee (The Journal of Knee Surgery, 2023)
This review discusses the correction of coronal deformity and intercompartmental imbalance through bone resection in total knee arthroplasty (TKA). To achieve functional knee balance, coronal, rotational, and sagittal alignment are critical to successful patient outcomes. Though variations in coronal alignment are debated as a correlate to positive results, advancements in utilizing implant position, alignment, and soft tissue balance to improve patient outcomes and function are an evolving discussion. This study draws upon existing literature, clinical studies, and surgical techniques related to TKA, including advancements in navigation and robotics. The study highlights the importance of individualized alignment strategies for varus and valgus knees. While mechanical neutral alignment has shown excellent long-term data, reevaluating the anatomic recreation of the patient's joint line obliquity is now being studied extensively. Sensor data and navigation systems contribute to improved outcomes and patient satisfaction. The evolution of navigation and robotics has led surgeons to achieve their target angles consistently and accurately; now, the discussion is around the most effective alignment targets. The classification of various phenotypes assists in the proposed starting points for implant position, but soft tissue tension is required in the input data to achieve global balance and stable motion. Each approach's advantages and limitations are considered. In conclusion, achieving optimal coronal alignment, joint line obliquity, and soft tissue balance is crucial for successful TKA outcomes. Personalized alignment philosophies, supported by three-dimensional data and sensor technology, are evolving to minimize critical errors and enhance functional results. Robotic assistance and future advancements in artificial intelligence and machine learning hold promise for further improving TKA outcomes in the quest for soft tissue stabilization.
Keywords: orthopaedics; total knee; robotics; ligament; balance